PENGEMBANGAN MEDIA SPARKOL VIDEO SCRIBE MENULIS TEGAK BERSAMBUNG TEMA 6 SUBTEMA 1 KELAS II SDN 1 KRADINAN - Kusuma Wardhani, Manggar; Devi Asriyanti, Frita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research on the development of sparkol video scribe media is motivated by the lack of learning media used during the learning process. Educators tend to use printed books in delivering materials. This research aims to develop, test the validity, and feasibility of the development product of sparkol video scribe media writing upright with theme 6 subtheme 1 grade II SDN 1 Kradinan. The method used in this study uses Research and Development (R&D) using the ADDIE development model which consists of 5 stages, namely Analyze, Design, Development, Implementation, Evaluate. The data collection technique was carried out by testing the validity of media, materials, and distributing questionnaires. The instruments used in this study used validation sheets of media experts, material experts, and student response questionnaires. The results obtained, media validation by validators were obtained with a percentage of 89% with a very valid category, material validator assessments were obtained 90% with a very valid category, student response assessments were obtained 90% with a very valid category. Thus, the results of this study can be concluded that